Obsession [large type] - Woods, Stuart; Battles, Brett (Woods, Stuart. Teddy Fay novel, 2023)
"While filming on location in scenic Santa Barbara, California, Peter Barrington and Ben Bacchetti look to expand Centurion Studios' business by making a deal with a young Croatian billionaire. But when the magnate's wife is kidnapped, Teddy Fay is brought in to assess the threat and recover the young woman. As Teddy unravels the threads of her disappearance, he quickly comes to find that darker forces are at play and an old vendetta has been revived that puts them all at risk. Meanwhile, danger lurks even nearer to home as an obsessive fan with perilous intentions weasels his way onto the film set, and only Teddy can stop him from getting too close for comfort"--